2008
DOI: 10.1016/j.jelechem.2008.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Formation of viologen radical cation condensed phase through two-dimensional molecular organization process on an HOPG electrode surface in binary viologen solutions

Abstract: Viologens possessing long alkyl chains are condensed to monolayers of their radical cations upon one-electron reduction on a basal plane of a highly-oriented pyrolytic graphite (HOPG) electrode in contact with not only one-component viologen aqueous solutions but also binary mixtures. For three types of binary mixtures of viologen including ten different combinations, the condensed phase formation processes were described using the results of voltammetric measurements. First, in the case of the binary mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…On the other hand, the adsorption properties of 4,4′-bipyridine have been studied. The adsorption prewave was observed in the acidic aqueous solutions of 4,4′-bipyridine and was explained by a two-dimensional (2D) condensed phase formation of the doubly protonated reduction product, i.e., of the cation radical. Similar interfacial behavior has been observed for the adsorption of dialkyl viologens on mercury, gold, silver, and highly oriented pyrolytic graphite , electrodes in the aqueous medium, where the 2D adsorption of the dialkyl viologen cation radical was confirmed. Additionally, Kobayashi et al showed that the methyl viologen (MV 2+ ) adsorbs on the mercury electrode with a flat orientation at more positive potentials than the potential of zero charge, whereas its reduced form MV +• (cation radical) adsorbs with a vertical orientation at the potentials more negative than the formal potential of the MV 2+ /MV +• redox couple.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…On the other hand, the adsorption properties of 4,4′-bipyridine have been studied. The adsorption prewave was observed in the acidic aqueous solutions of 4,4′-bipyridine and was explained by a two-dimensional (2D) condensed phase formation of the doubly protonated reduction product, i.e., of the cation radical. Similar interfacial behavior has been observed for the adsorption of dialkyl viologens on mercury, gold, silver, and highly oriented pyrolytic graphite , electrodes in the aqueous medium, where the 2D adsorption of the dialkyl viologen cation radical was confirmed. Additionally, Kobayashi et al showed that the methyl viologen (MV 2+ ) adsorbs on the mercury electrode with a flat orientation at more positive potentials than the potential of zero charge, whereas its reduced form MV +• (cation radical) adsorbs with a vertical orientation at the potentials more negative than the formal potential of the MV 2+ /MV +• redox couple.…”
Section: Introductionsupporting
confidence: 76%
“…E-mail: hromadom@ jh-inst.cas.cz. (15) G omez, L.; Ruiz, J. J.; Camacho, L.; Rodrı´guez-Amaro, R. silver, 27 and highly oriented pyrolytic graphite 28,29 electrodes in the aqueous medium, where the 2D adsorption of the dialkyl viologen cation radical was confirmed. Additionally, Kobayashi et al 17 showed that the methyl viologen (MV 2þ ) adsorbs on the mercury electrode with a flat orientation at more positive potentials than the potential of zero charge, whereas its reduced form MV þ• (cation radical) adsorbs with a vertical orientation at the potentials more negative than the formal potential of the MV 2þ /MV þ• redox couple.…”
Section: Introductionmentioning
confidence: 94%
“…Such redox-active monolayers can, for instance, be formed by viologens, which are among the most intensively studied molecular building-blocks in supramolecular chemistry [1]. Their solution electrochemistry is well documented in literature [8][9][10] and the surface chemistry has been investigated over the past years by electrochemical methods such as Cyclic Voltammetry [11][12][13], STM [14][15][16][17][18][19] and spectroscopic methods like Raman spectroscopy [20][21][22][23][24][25][26] and UV/IR reflectance spectroscopy [27][28][29][30][31][32]. However, only a few reports combine microscopic and spectroscopic methods [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…These transitions are quite sharp. The sharp phase change accompanied by the redox of viologen is caused by strong attractive interaction between neighboring V .+ units. In addition, alkyl chain‐chain interaction, [65,66] hydrogen‐bonding [67–69] and interaction with anions [70] closely participate the factors to change the midpoint potential and the peak separation. In other words, the pattern of the sharp redox peaks is an indicator how the various intermolecular interactions work concertedly between V .+ ‐forms, together with the viologen‐electrode substrate interaction.…”
Section: Powering and Dynamics By Redoxmentioning
confidence: 99%